PERANCANGAN PRODUK INTERIOR DAN BOOTH DENGAN PENDEKATAN KEARIFAN LOKAL - Gunung, Luh De Risa Agustin Dharma; Nuradhib, L Maureen; Rahadiyanti, Melania (Aksen : Journal of Design and Creative Industry, 2020)
This article contains the product design and booth for the Luhde Risa company which is made as a business preparation for the author in the future. The business focus taken by the author is modern local wisdom. The concept of local wisdom carried by the author focuses on the traditions and wealth of Indonesia. The author designs interior products and booths with a local wisdom approach in Bali. The purpose of this design is to maintain and enhance Indonesian local wisdom in the form of interior products, create products that are able to follow trends but still maintain local wisdom, become a provider of the need for space contents that can help consumers in completing space needs, becoming a company that is able to compete globally, increasing world achievement in the field of creative industries, especially the furniture industry. This design uses exploration, observation and analysis of Indonesian resources as a reference in designing interior products. The design of the booth is based on the results of the market survey obtained through the results of personal analysis. Exploration, observation and analysis were obtained from several articles, resource persons conducted through interviews with similar competitors and market surveys through questionnaires. Using the potential of natural resources from Indonesia which has the potential to develop this business so that it is expected to be able to provide a positive response to the economic development of Indonesia and globally.